Was It a Case of “Flatbush Diabetes” with Severe Hypertriglyceridemia? - Al-Nuaimi, Mouza Mohammed; Ismail, Mohamed Milad; Elhouni, Ali (Ibnosina Journal of Medicine and Biomedical Sciences, 2022)
We present a case of a morbidly obese 27 years male patient who was admitted with sudden onset abdominal pain and crashed into diabetic ketoacidosis as new-onset diabetes and discuss the possible etiology of this combined picture of acute pancreatitis and severe hypertriglyceridemia. Flatbush diabetes was, meanwhile, thought of due to his morbid obesity that in turn raised our suspicion of acute insulin-requiring type 2 diabetes mellitus versus T1 diabetes mellitus. Ketosis-prone diabetes or Flatbush diabetes is a syndrome in which diabetes commences with ketoacidosis in patients who are glutamic acid decarboxylase and antiislet cell antibody negative and have no known precipitating causes. They are usually middle-aged, overweight, or mildly obese, and in many reports, they are likely to be male with a family history of type 2 diabetes mellitus; they present with new-onset severe hyperglycemia and ketosis or frank diabetic ketoacidosis. After intensive initial insulin therapy, many patients become insulin-independent and can be well controlled on diet plus oral medications or, more rarely, diet alone.
Keywords: Flatbush; hypertriglyceridemia; ketoacidosis (DKA); insulin